Change of Radial Gap Value in Axial Compressors at Modes of Turbine Plant Heating and Shut-Down - A. S. Laskine; V. V. Isaev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Designing of highly-efficient axial compressors is connected with their better aerodynamic cleanness. One of the ways is to minimize radial clearances for decreasing leakages and, consequently, increasing efficiency. At the same time it is necessary to exclude stator touching by rotor blades.ANSYS complex has been used to reduce a gap by 1.5–2.0-fold in comparison with the existing one.It has become possible to obtain dependences of radial displacement of peripheral blade edge and stator ring element, located above it, on heating time.Practical and research value of the paper is in the development of a methodology for calculation of heating (cooling), which can be applied while designing axial turbine machines and evaluating the possible minimization of radial gap in the case that excludes touching.